Analysis of the Structural Performance of the State Treasury Services Office Building Against the Latest Earthquake Regulations SNI 1726 - 2019 - Andika, Feri; Simbolon, Ronal H T; Hasibuan, M Husni Malik (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the structural performance of the Tanjung Balai State Treasury Services Office Building (KPPN) against the latest earthquake provisions in SNI 1726-2019. This analysis is important to ensure that existing building structures meet the latest regulations and are able to withstand anticipated earthquake loads. The research methodology includes collecting building technical data, structural modeling using SAP2000. Building technical data includes information regarding dimensions, materials and main structural elements. Structural modeling is carried out to create a digital representation of the building. The results of the structural analysis program show that the natural period value according to both regulations and modeling is 0.196769 seconds. The basic earthquake force obtained from SNI 1726-2019 is 51,314 kN for the However, the base reaction is considered safe in both regulations because of the static earthquake force, namely 38,962 kN for SNI 1726-2019 and 31.17 kN for SNI 1726-2012. Then the story drift in the X direction of SNI 1726-2019 is 0.114 mm, in the Y direction 0.437 mm with a clearance deviation of 80 mm. And SNI 1726-2012 X direction 0.096 mm, Y direction 0.3 mm with a clearance deviation of 80 mm. According to the ATC-40 analysis which was analyzed using SAP2000 software, the building performance that occurs on soft soil (SE) has a drift value of 0.015 which is included in the Damage Control phase. From the results of this analysis, it can be concluded that the Tanjung Balai State Treasury Services Office Building (KPPN) meets the security criteria in accordance with SNI 1726-2019. These findings are expected to provide valuable recommendations for building owners to ensure the safety and suitability of existing building structures against earthquake risks in Indonesia.